An Overview on Advance Psychoneurobics: The Path towards Personal Growth and Interconnectedness (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For centuries we have known the capacity of the intensity of the Individual. However our occidental training has disconnected us from the source, having made an intense awkwardness of people to their relationship and interconnectedness to nature and themselves. Psycho-Neurobic science as it was divined to Dr. Chandrasekhar Tiwari Ji is intended to enable the restoration of people bury connected ness to nature by bringing out the intensity of expectation as a living, continuing and flourishing route forward. Investigations with water as a receptor mode for examination uncover the water's reaction to human expectation. Presentation The idea of extreme reality guides us to the rhythms of Energy, Light, Information and Life, which is exemplified in the vehicle of WATER the characteristic substance that gives rich substance informational indexes on recurrence and vibration engraves which is estimated by means of this trend setting innovation of Bio-Electrography and Electro Photonics. The goal is to give down to earth applications and arrangements that will honor the human network towards resuscitating the personal satisfaction unto one self and to the worldwide network. Strategies In psycho-neurobic's, as divined to Dr. Chandrasekhar Ji, inward refinement is the basic texture in making a vast expanse of wholeness.